(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Question: What is the newest element of alien species, of the urban flora? Locations: Kyiv urban agglomeration (KUA), 13534 км². Methods: critical analysis of literature, own observations and photographs in nature, information from the iNaturalist database. Nomenclature: POWO 2023, Mosyakin, 2013. Results: During the period 2002–2023, there were significant changes in the urban flora of the KUA: it was replenished with 85 alien species from 63 genera and 43 families, these are escaped ornamental or weed plants. The vast majority of them are ergasiophytes – 86%; in addition to 7 xenophytes, 4 presumably native species with a progressive range type, 1 previously unnoticed due to low presence, together about 14%. The source of escaped plants is landscaping, urban and amateur floriculture, introduction centers, etc. The unstable component of the newest element is 79% (ephemerophytes – 33%, colonophytes – 46%). Ergasiophytesephemerophytes are in the immigration stage of establishment, the formation of normal populations, the strengthening of presence in the area, and the maintenance of the territory continue. The changes in the urban flora are reversible, the species and typological state of the newly discovered element is extremely favorable for the introduction of a preventive system of early recognition, timely response and prevention of the negative impact of alien species within the Kyiv urban agglomeration on native species, their communities, biotic diversity and quality of life. There is an urgent need to create a national database regarding alien species of plants, which would include operational scientific information, public education and administrative measures. Conclusions: Precautionary administrative measures should be taken, such as a ban on the import of seeds and planting material of invasive ornamental plants, trade in them, and introduce operational information and education of the population regarding the treatment of alien species of plants.